2013
DOI: 10.1123/rsj.37.1.66
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Perceived Benefits of Participation between Recreational Sport Programs

Abstract: This study examined recreational sports, with a focus on a comparative analysis of the overall, social, intellectual, and fitness perceived benefits associated with participation in three separate recreational program areas: group fitness, intramural sport, and sport clubs. A survey instrument, based upon the Task and Ego Orientation in Sport Questionnaire (TEOSQ) and Quality and Importance of Recreational Services (QIRS) perceived benefit scale, was administered to 1,176 students at a postsecondary institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 28 publications
1
44
1
1
Order By: Relevance
“…Additionally, participation in sport clubs can be characterized by purposeful engagement. Club members pay dues, attend regular practices, and possibly participate in extramural competition, with many teams instructed by a coach or captain (Lower et al, 2013;Mull, Bayless, & Jamieson, 2005). The additional responsibility of club operations, meetings, and practice is likely to enhance task-and self-based achievement goals.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, participation in sport clubs can be characterized by purposeful engagement. Club members pay dues, attend regular practices, and possibly participate in extramural competition, with many teams instructed by a coach or captain (Lower et al, 2013;Mull, Bayless, & Jamieson, 2005). The additional responsibility of club operations, meetings, and practice is likely to enhance task-and self-based achievement goals.…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified sport club meetings (Ramos et al, 2018), club practices and competition (Haines & Fortman, 2008; Lower et al, 2013; Warner & Dixon, 2012), club travel (Haines & Fortman, 2008), club social events (Czekanski & Lower, 2019), and student leadership activities (Flosdorf et al, 2016; Lower et al, 2013; Warner & Dixon, 2012) as contributors to the social outcomes of sport club participation. However, past research examining outcomes of sport club participation is largely anecdotal and does not empirically test the relationships between distinct sport club activities and student outcomes.…”
Section: Collegiate Sport Clubs Contribution To Attachmentmentioning
confidence: 99%
“…In collegiate sport clubs, student members celebrate competitive successes, socialize off the field of play, and cultivate long-term bonds with teammates and the institution. Previous research has demonstrated the importance of sport club programs to the overall well-being of students on a university campus (Beyer & Hannah, 2000; Lower et al, 2013; Warner & Dixon, 2012). However, little is known about the sport club mechanisms that contribute to student well-being and success.…”
mentioning
confidence: 99%
“…Results from the principal component analysis found the three subgroups: social, intellectual, and fitness, to account for 68.59 percent of the variance, while the confirmatory factor analysis indicated a good fit (RMSEA: .09; NFI: .98; CFI: .98). The structure of the scale, however, has been found to vary across empirical studies (Forrester & Beggs, 2005;Lower, Turner, & Petersen, 2013).…”
Section: Instrumentationmentioning
confidence: 99%